A Model for the Process of Idea Generation. (4th March 2017) - Sarkar, Prabir; Chakrabarti, Amaresh
Abstract: A variety of models of design and idea generation exist; yet, the exact process of idea generation is still only vaguely understood. In this paper, we propose a model of the idea generation process and make a number of recommendations for its improvement. We study both novice and experienced designers through a series of design experiments, seek patterns in their search for ideas, and use these to model the process. A major finding is that designers rely heavily on existing designs from their memory and modify these suitably to develop solutions for a given problem. Further, we discuss various specific patterns of idea generation during conceptual design.